Patient Satisfaction and Experiences towards Paramedical Services in a Secondary Care Referral Healthcare Setting of India - Bogireddy, Sahithi; Rathinavelu, Mohanraj; Kalimuthu, Rajeswari; Reddy, Yiragamreddy Padmanabha (Indian Journal of Pharmacy Practice)
Background: Healthcare organization is a sector where patient is the main focus where improving the patient outcome is the imperative function. Patient satisfaction survey helps in evaluating the quality of the services provided by the hospital. Objective: The current prospective observational (survey-based) study of six months duration aimed in evaluating the patient experience and satisfaction towards the paramedical services provided in a healthcare setting of south India. Methods: A standard and validated questionnaire on paramedical services was designed consisting of 32 questions reviewed by the nurses and pharmacists, for the simplicity, reliability and clear understanding of the patients relating to various aspects that influence the patient satisfaction. The questions had been scored ranging from 1-5 based on the satisfaction levels. A proper information consent was made during data collection by clearly explaining the patients about the study. Results: In 250 patients, the study participant responded 49.2% of satisfaction towards patient centered pharmaceutical care services, 43.6% of satisfaction towards nursing care service, 52% and 53.6% of satisfactory level towards nutrition and laboratory services respectively. In our study, the overall response of the patient about paramedical services was satisfactorial. Conclusion: In conclusion, the principles of patient centered paramedical care services has to be implemented and practiced to achieve better health outcome and patient satisfaction.
Keywords: Patient satisfaction survey; Paramedical care services; Nutritional services; Nursing care services; Pharmaceutical care services; Survey